Influência dos cimentos endodônticos e agentes de cimentação na resistência à união de pinos de fibra de vidro - Borges, Adriana Fonseca (2009)
The compatibility among different root canal sealers and luting agents for post cementation is an important aspect that must be considered in the prosthetic rehabilitation. This study evaluated the effect of different root canal sealers on the bond strength of fiberglass posts luted with four different luting agents. One hundred and thirty one human canines were selected, the crowns removed and the roots instrumented. For obturation, the specimens were randomly divided into 3 groups (n=44) accordingly to the root sealers: E - zinc oxide and eugenol-based; H -calcium hydroxide-based and R -resinous cement. Then, root canals were prepared with a drill of the post system. The initial groups were subdivided into four subgroups (n=11) accordingly to the luting agents for the cementation of posts: P - zinc phosphate cement, I -resinmodified glass ionomer cement, RC -resin cement and RA - self-adhesive resin cement. Roots were cross-sectioned to obtain six 1-mm-thick slices that were submitted to micropush-out test. Data were analyzed using ANOVA and Tukey tests. The interaction among root canal sealer, luting agent and region of the root had significant effect on the bond strength of fiberglass posts (P<0.05). Zinc oxide and eugenol-based cement interfered negatively with the bond strength to root dentine when conventional and self-adhesive resin cements were used along its full length. Lower bond strength values were obtained with the interaction between zinc oxide and eugenol and conventional resin cement, while higher values were obtained with the interaction between calcium hydroxide and self-adhesive resin cement. Bond strength decreased from crown to apex only in resin cement groups.